Price Liberalization in Russia : The Early Record - Koen, Vincent (IMF Working Papers; Working Paper ;, 1992)
Prices in Russia have been decontrolled in several steps since early 1991, after decades of near-fixity. Their behavior before and after the January 1992 price liberalization is analyzed here, as are the associated movements of wages and overall consumer incomes and expenditures. The emphasis is on developments in the first half of 1992. Comparisons are made with recent experience in Eastern Europe. Evidence on shortages, saving and income distribution is also considered.